2006
DOI: 10.1063/1.2172734
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency microcavity top-emitting organic light-emitting diodes using silver anode

Abstract: Top-emitting organic light-emitting diodes (TOLEDs) employing highly reflective Ag as anode and semitransparent LiF∕Al∕Ag as cathode were fabricated. The hole injection efficiency of Ag anode can be significantly improved with surface modification using a CF4 plasma. With C545T-doped Alq3 emitter, the top-emitting device shows a low turn-on voltage of 2.65V. The optimized microcavity TOLED shows a current efficiency enhancement of 65% and a total outcoupling efficiency enhancement of 35%, compared with a conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 20 publications
(19 reference statements)
0
68
0
Order By: Relevance
“…A semitransparent metal electrode such as a thin Ag layer is mostly commonly used due to its simple fabrication steps. 4,11,[13][14][15] However, a thin Ag layer does not provide a high enough reflectivity for a microcavity device. Because of the large extinction coefficient of a metal and of the presence of surface plasmon mode at the organic/metal interface, the use of semitransparent metal electrodes is not favorable for microcavity OLEDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A semitransparent metal electrode such as a thin Ag layer is mostly commonly used due to its simple fabrication steps. 4,11,[13][14][15] However, a thin Ag layer does not provide a high enough reflectivity for a microcavity device. Because of the large extinction coefficient of a metal and of the presence of surface plasmon mode at the organic/metal interface, the use of semitransparent metal electrodes is not favorable for microcavity OLEDs.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] In addition, it has been reported that microcavity structure can be used to enhance the light extraction of an OLED by modifying the light distribution within the device. [4][5][6][7] However, closely examining the previous reports, there is a significant difference in luminance enhancements in different microcavity OLEDs. While two times enhancement in current efficiency has been observed in green microcavity OLEDs, no significant improvements were reported in blue microcavity devices.…”
Section: Introductionmentioning
confidence: 90%
“…It can be seen that they both turn on at about 3V, and reach 100 cd/m 2 at ~ 4.5 V. At higher voltages, the top-emitting OLED shows better L-V characteristics than the bottom-emitting one. This is attributed to out-coupling enhancement due to the microcavity structure [15]. Further evidence can be found in the EL spectra comparison as shown in Fig.…”
Section: Resultsmentioning
confidence: 48%
“…The whole stack was completely finished with the "noninverted" top-emitting OLED preparation on top of the middle electrode with the same structure as the bottom one except that the topmost silver layer was semitransparent for achieving better light out-coupling efficiency [15]. The bottom ITO anode, middle composite silver electrode and top semitransparent cathode can be individually connected to external power lines so as to measure separately the EL performance of bottom-and top-emitting OLED.…”
Section: Methodsmentioning
confidence: 99%
“…However, Ag anode has poor hole-injection property due to its low work function (∼4.3 eV) [5,6]. A number of attempts have been conducted to enhance the hole-injection property of anode, such as inserting a high work function metal oxide buffer layer between anode and organics as the hole-injection layers (HILs) [7][8][9]. Copper oxide (CuOx) is a transparent conducting oxide [10].…”
Section: Introduction 1)mentioning
confidence: 99%